ENGLISH DAILY NEWSPAPER AND ITS IMPACT ON PROFESSIONAL LITERACY FOR ENGLISH LECTURER - Jasuli, Jasuli (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2018)
The present study aims at finding the impacts of English daily newspaper on the development of professional literacy for lecturer. The literate daily habit of English lecturers is the underlying reason why this study is carried out. The literate habits can be found where lecturers used to be reading printed mass media written in English besides reading other primary textbooks and references. They designate The Jakarta Post mass media which is the biggest mass media in Indonesia written in English. As the study focuses on how the daily newspaper contributes to their professional literacy, a qualitative descriptive research design is used to execute the study. The respondents are English lecturers of Teacher Training and Education (IKIP) Budi Utomo Malang consisting of seventeen lecturers. The data is gained through observation and interview. Based on the data analysis, it is found that English daily newspaper has impacts on lecturers' professional literacy. Respondents were challenged to how Indonesian phrases are expressed in English. They are also challenged to be more critical reader, both editing and content critical based. While on their duties of Tridharma, the newspaper is leveraged as classroom supplements for teaching language skills and components as well as linguistics and literature studies. Their writing stamina also boosted as their input from the news increased. Finally, their experiences are very often expressed in their last Tridharma duties, i.e. public services by sharing and upgrading teachers' literacy at schools.